A Research Note on Challenges of Cross-National Aging Research: An Example of Productive Activities Across Three Countries. (January 2018) - Chen, Yu-Chih; Wang, Yi; Cooper, Ben; McBride, Timothy; Chen, Huajuan; Wang, Dongmin; Lai, Ching-Ying; Montemuro, Lauren C.; Morrow-Howell, Nancy
Cross-national studies can elucidate the influence of sociocultural contexts on a wide variety of aging issues. This study aims to develop methods for using secondary data for cross-national comparisons using productive activities as an example. The study also identifies challenges in conducting cross-national research. Using the national representative data from the United States, China, and South Korea, this study developed a sequence of methods for cross-national analysis. Results indicate that productive activities vary by country, and this variation could possibly be due to the differences in sociocultural context and variations in operationalization and measurement. Given the difficulty of making decisions and drawing conclusions across different cultural contexts, team members must include scholars who are familiar with the culture and language of the region of study. Researchers also need to determine whether data sets are valid for cross-national comparisons and understand the limitations of the comparisons, given constraints in the data.